Divergent Thinking Influences the Perception of Ambiguous Visual Illusions. (May 2021) - Blake, Annabel; Palmisano, Stephen
This study investigated the relationships between personality and creativity in the perception of two different ambiguous visual illusions. Previous research has suggested that Industriousness and Openness/Intellect (as measured by the Big Five Aspects Scale) are both associated with individual differences in perceptual switching rates for binocular rivalry stimuli. Here, we examined whether these relationships generalise to the Necker Cube and the Spinning Dancer illusions. In the experimental phase of this study, participants viewed these ambiguous figures under both static and dynamic, as well as free-view and fixation, conditions. As predicted, perceptual switching rates were higher: (a) for the static Necker Cube than the Spinning Dancer, and (b) in free-view compared with fixation conditions. In the second phase of the study, personality type and divergent thinking were measured using the Big Five Aspects Scale and the Alternate Uses Task, respectively. Higher creativity/divergent thinking (as measured by the Alternate Uses Task) was found to predict greater switching rates for the static Necker Cube (but not the Spinning Dancer) under both free-view and fixation conditions. These findings suggest that there are differences in the perceptual processing of creative individuals.